Total Parenteral Nutrition: The Long and The Short of It - Duna Penn (Indonesian Pediatric Society, 1996)
Within 30 years of Harvey's discovery of the circulatory system, attempts were made to utilize intravenous routes for nutrient administration.1 In 1656, Sir Christopher Wren infused wine into the veins of dogs via goose quills attached to a pig's bladder. Over the ensuing years, salt and sugar solutions, milk, olive oil, egg whites, and in later times, protein hydrolysates were tried with varying degrees of success. However, it was not until the 20th century that total parenteral nutrition (TPN) began to be viewed as a realistic therapeutic modality, stimulated by Wilmore and Dudrick's report of normal growth in a young infant with extensive intestinal atresia who was successfully mainÂtained on intravenous nutrition for over 6 weeks.2 Since then, there have been many advances and refinements, including the development of specialized crystalline amino acid solutions and lipid emulsions. Further investigation is currently underway to determine the effect of